Spatiotemporal co-circulation of four dengue serotypes across Mexico, 2020–2025: A space-time scan analysis - Oliver Mendoza-Cano; Xóchitl Trujillo; Mónica Ríos-Silva; Jaime Alberto Bricio-Barrios; Agustin Lugo-Radillo; Rosa Tapia-Vargas; Jesús Venegas-Ramírez; Eder Fernando Ríos-Bracamontes; Herguin Benjamin Cuevas-Arellano; Yolitzy Cárdenas; Raúl Aquino-Santos; Iris Anecxi Jiménez-Vieyra; et al. (PLoS ONE, 2026)
Background Mexico has experienced escalating dengue transmission driven by the co‑circulation of four antigenically distinct serotypes (DENV‑1 through DENV‑4). Multi‑serotype transmission is epidemiologically relevant, yet its spatiotemporal patterns at sub‑national resolution remain poorly characterized. Methods We analyzed 103,426 PCR‑confirmed, serotyped dengue cases across 1,547 of 2,471 Mexican municipalities from January 2020 to December 2025. Kulldorff’s space‑time scan statistic under a discrete Poisson model was applied independently to each serotype and to all serotypes combined. Co‑circulation was defined as the spatiotemporal overlap of significant clusters from at least two serotypes within the same municipality for ≥ 1 epidemiological week. Results We identified 159 statistically significant clusters across all serotypes combined. DENV‑3 was dominant (64.4% of cases; annual incidence 59.9/100,000), consistent with the reemergence of a long‑absent serotype. The 2024–2025 season produced a nationally synchronized epidemic across geographically distant regions. Co‑circulation of at least two serotypes occurred in 1,545 municipalities; 217 experienced simultaneous clustering of all four serotypes. Active co‑circulation was present in 275 of 311 study weeks. Mean pairwise temporal overlap ranged from 8.0 to 12.0 weeks, with maximum overlaps of 29–30 weeks. Conclusions Four‑serotype co‑circulation was documented at municipal resolution, concentrated in the Gulf coast, the Yucatán Peninsula, and northeastern Mexico. The 217 municipalities with simultaneous clustering of all four serotypes may represent areas of epidemiological interest for further investigation. This municipality‑level spatiotemporal framework offers operationally relevant resolution for tracking multi‑serotype activity and supporting serotype‑aware dengue monitoring at sub‑national scale.